Government education expenditures in early and late childhood - Abington, Casey; Blankenau, William F. (My University, 2013)
Human capital investment in early childhood can lead to large and persistent gains. Beyond this window of opportunity, human capital accumulation is more costly. Despite compelling evidence in support of this notion, government education spending is allocated disproportionately toward late childhood and young adulthood. We consider the consequences of a reallocation using an overlapping generations model with private and public spending on early and late childhood education. Taking as given the higher returns to early childhood investment, we find that the current allocation may nonetheless be appropriate. When we consider a homogeneous population, this can hold for moderate levels of government spending. With heterogeneity, this can hold for middle income workers. Lower income workers, by contrast, may benefit from a reallocation.
Keywords: Government education expenditures; Human capital; Heterogeneous agents; Life-cycle model